Method for obtaining a carrier for a hydrorefining catalyst, carrier for a hydrorefining catalyst, hydrorefining catalyst, method for obtaining a hydrorefining catalyst and use of a carrier in a hydrorefining catalyst
By using the acid route preparation method of aluminum sources, organic acids and boron sources in the hydrorefining catalyst, the problem of boron additives being easily leaching in industrial equipment is solved, the activity and stability of the catalyst is improved, and environmental pollution is reduced. Improve the production efficiency of the hydrotreatment process.
Patent Information
- Application Number
- CN202080097381.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-27
- Filing Date
- 2020-12-17
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2040-12-17
AI Technical Summary
In the prior art, additives based on chemical element boron are easily leaching under the starting and operating conditions of industrial hydrogen refining equipment, resulting in a reduction in catalytic activity and stability, and the loss of boron causes pollution to the environment.
Through innovative preparation routes, combining acidic route methods of aluminum sources, organic acids and boron sources, carriers are prepared to reduce the leach loss of boron and fix boron in the catalyst to ensure its activity and stability in the hydrorefining reaction.
It significantly increases the activity and stability of the catalyst, reduces the environmental release of boron, reduces pollution, maintains the operating characteristics of the catalyst, and improves the production efficiency of the hydrorefining process.
Smart Images

Figure BDA0003810695410000121 
Figure BDA0003810695410000131
Abstract
Description
Technical Field
[0001] The present invention relates to a method for obtaining a support for hydrorefining catalysts by an innovative route, aiming to reduce the leaching losses of additives based on the chemical element boron and its chemical derivatives and / or the related loss processes. Hydrorefining catalysts for treating streams from petroleum fractions and their combination with renewable streams (biomass in the natural state and / or obtained from previous treatments) and / or streams obtained in Fischer-Tropsch type processes containing boron-based chemical derivatives have been used to improve the performance of hydrocracking reactions (HCC), hydrodenitrogenation (HDN), hydrodesulfurization (HDS), olefin hydrogenation (HDO), metal removal or hydrodemetallization (HDM), hydrogenation of aromatic compounds (HDA) and other processes involving catalysis at hydrogenation, hydrogenolysis and / or acid sites. Background Art
[0002] Over the years, the oils processed in refineries have become heavier (°API lower) and higher in pollutants (olefins, sulfur, nitrogen, metals) and aromatics. In this way, an increase in the yield of heavy fractions relative to light distillates (naphtha) and medium distillates (kerosene and diesel) has been observed. At the same time, environmental regulations have tightened quality limits, mainly regarding limits on the sulfur and aromatics content in fuels.
[0003] In view of this situation, the demand for technical solutions for improving the quality of oil fractions (naphtha, kerosene and diesel) by hydrotreating processes (HDT) and for converting heavy fractions (diesel and residues) into high value-added products (naphtha, kerosene, diesel, marine fuel, lubricating base oils and paraffins) by catalytic hydrocracking (HCC) processes in oil refineries is increasing. The transition to a low-carbon economy has also promoted the development of hydrofining processes for treating charges containing renewable content (biomass in the natural state and / or biomass obtained from previous treatments). Hydrofining of streams obtained from the Fischer-Tropsch process also contributes to the production of excellent quality fuels, lubricating base oils and paraffins. In addition to hydrocracking (HCC), these solutions have also undergone research and development of more active (high conversion and selectivity) and more stable (low deactivation rate) catalysts for metal removal or hydrodemetallization (HDM), olefin hydrogenation (HDO), hydrodesulfurization (HDS), hydrodenitrogenation (HDN) and hydrogenation (HDA) reactions of aromatic compounds.
[0004] Catalysts for diesel hydrocracking maximize their performance by optimizing the balance of hydrogenation (metal, reduction or sulfidation sites) and acidity (acidic support such as silica-alumina or zeolites, or additives containing the acidic function responsible for cracking) functions.
[0005] In this regard, studies have shown that conventional catalysts (composed of mixed sulfides of NiMo and CoMo) can be improved when different supports (e.g., carbon / carbide, silica, titania, zirconia, and zeolites) are used compared to conventional γ-Al2O3. Mixtures SiO2-Al2O3, SiO2-TiO2, and ZrO2-Al2O3 have also been considered due to their excellent acid-base properties. Recently, many catalysts have been supported on B2O3-Al2O3 mixtures due to the higher acidity provided by boron.
[0006] From this point of view, the prior art describes that the addition of boron in the form of chemical derivatives based on the chemical element boron to alumina used as a support for sulfided NiMo and CoMo catalysts improves the catalytic performance for hydrocracking reactions (HCC), hydrodenitrogenation (HDN) and hydrodesulfurization (HDS). Maity et al. (Effect of preparation methods and content of boron on hydrotreating catalytic activity, Energy Fuels 2011, 25, 3100-3107) evaluated the effect of boron addition on alumina-supported NiMo catalysts, in which the active metal phase and additives were incorporated into the support by an impregnation technique.
[0007] The addition of boron produced a catalyst with greater dispersion of the metal phase and the active phase (MoS2). This improvement was attributed to the formation of a boron monolayer on the alumina surface, which reduced the interaction between the metal phase and the support.
[0008] The performance of boron-additive catalysts for thiophene hydrodesulfurization, cumene hydrocracking, diesel hydrodesulfurization, petroleum hydrodesulfurization, and hydrodemetallization reactions was evaluated.
[0009] The boron-containing catalysts showed higher cumene hydrocracking and thiophene hydrodesulfurization activities, indicating an increase in their acidic functionality. In addition, it was demonstrated that the presence of boron can help reduce catalytic deactivation during hydroprocessing of heavier fractions and increase catalyst stability (longer run time).
[0010] Several patents (US 20120065056 A1, CN 103100390 A, US 7837960 B2, CN101332430A, US7879224B2 and CN 102989493A) show improvements in metal site distribution (hydrogenation function) and increase in acid strength (hydrogenation function) when using boron as an additive for hydrofinishing catalysts (hydroprocessing for fuel production and hydrocracking of diesel and residues).
[0011] Similarly, Chen and Tsai, Catalysis Today 50 (1999) 57-61, evaluated CoMo and NiMo catalysts loaded with different aluminum / boron ratios in hydrodesulfurization and hydrodemetallization (HDM) reactions. In these tests, it was found that in the presence of boron, for both CoMo and NiMo catalysts, the hydrodesulfurization activity was improved, making the catalyst more active. The document states that for maximum activity, the best B2O3 content is 4 mass %. In this case, considering the removal of nickel and vanadium, the same boron value is shown for maximum hydrodemetallization activity.
[0012] From the same perspective, as an improved option for hydrocracking, hydrotreating, hydrodesulfurization and / or hydrodenitrogenation processes, documents PI 00107603, US 4756822, US 4672049, US 5609750 and WO 2011036862 mention supported catalysts containing boron and / or boron-doped alumina.
[0013] However, despite the advantages associated with the use of boron, catalysts with boron additives have a disadvantage in that they are susceptible to leaching under start-up and operating conditions of industrial hydroprocessing plants. This aspect results in a reduction in the benefits provided by the addition of boron, a reduced increase in activity (hydrogenation and acidity) and a reduced stability (deactivation) of the catalyst over time.
[0014] Document US4034061 confirms the fact that boron is easily leached, mentioning that a catalyst based on boron-alumina may easily lose boron. The document shows that when calcined at 982°C and then subjected to steam passing at 200°C for 16 hours, the support loses 2.3% of the initial boron content, and when calcined at 1204°C for 1 hour, it loses 13.3% of the initial boron content. When leached for 2 hours in boiling water, it loses 6.4% of the initial boron content, and finally, when subjected to leaching for 2 hours in boiling water and then leached for 1 hour in ammonia solution, it loses 14.3% of the initial content. The solution presented in the document does not reduce the boron leaching process, it only involves the removal of free boron from the catalyst, and the presence of free boron is undesirable for the process.
[0015] Similarly, Dubois and Fujieda (Effects of boron in Co-Mo / B-Al2O3 hydrotreatmentcatalysts.Catalysis Today 29 (1996) 191-195) prepared a catalyst for hydrocracking middle distillates, which has 0 mass % to 10 mass % B, 10 mass % Mo and 3 mass % Co, wherein the carrier is obtained by physically mixing and extruding alumina with boron, and then drying and calcining. The results show that higher concentrations of boron produce greater cracking activity, which is related to the increase in alumina acidity due to the presence of boron. With regard to hydrodesulfurization function, its activity increases slightly, while for hydrodenitrogenation, the activity increase is significant. Despite the beneficial effect, the same document shows that after 16 hours of extraction, the original boron content of the catalyst is reduced from the original 3.7 mass % to a value close to zero, and in only two hours of extraction, the original content drops to 1.7 mass %. This effect is still prominent on uncalcined carriers. Thus, despite pointing out the beneficial effects of boron, the aforementioned literature does not suggest a method for reducing boron losses during the aforementioned processes.
[0016] In addition to the above problems, boron leaching has other disadvantages; in this regard, Becker et al. (Identification of the thermal decomposition behavior of ammoniumpentaborate-Thermochimica Acta, 235, 211, 2004) reported that borates and ammonium salts can be formed by the reaction of boric acid, ammonia and water. In a hydrofining plant, ammonia is formed by the hydrodenitrogenation reaction of nitrogen-containing compounds present in the feed, water is added at different steps of the process, and as boron is leached from the catalyst, conditions are created for the formation of this salt, which can precipitate in the cooler parts of the plant, which can cause a large loss of feed and require plant downtime, resulting in a loss of production and profitability of the refinery.
[0017] Another disadvantage associated with boron leaching is the exposure of the environment, animals and humans to the harmful and toxic effects of boron (KR Olson, Poisoning and drug overdose, 6th edition, Chapter 34, McGraw Hill). In the production of medical and food grade paraffins and lubricating base oils, a hydrofinishing step is necessary (for saturation of polycyclic aromatic compounds that are harmful to human health). In these industrial plants, hydrofinishing catalysts are used. The development of hydrofinishing catalysts with low boron leaching helps to maintain the advantages generated by this addition and reduce the possible exposure of the environment, animals and humans to harmful agents.
[0018] In an attempt to propose more alternative methods for incorporating boron, patent WO2010121807 describes a method for preparing a catalyst comprising at least one metal from group VIB and one metal from group VIII, a component having phosphorus and a component having boron, wherein the phosphorus represented by P2O5 and the boron component represented by B2O3 are both at least 1% by mass relative to the total weight of the catalyst. The catalyst is prepared by coextruding boron with a carrier, drying and calcining the extrudate, and then impregnating with a solution comprising phosphorus and a metal from group VIB and a metal from group VIII. Coextrusion is superior to the impregnation process because it allows higher levels of boron in the final catalyst and requires only one calcination stage instead of multiple steps. Therefore, despite the proposed method of incorporating higher levels of boron, the referenced document fails to propose a solution for the leaching process of this additive.
[0019] Still in this context, other work in the cited literature is valid, which uses aluminum nitrate, boric acid and ammonium hydroxide in the synthesis of hydrotreating catalysts, using conventional methods for the preparation of aluminum oxide, in which one of the steps includes boric acid, however, does not involve methods for reducing boron leaching (MCTsai and YW. Chen, Eng. Chem. Res. 1991, 30, 1801-1810 and Eng. Chem. Res. 1994, 33, 2040-2046.
[0020] In this context, it was determined that the conventional method of adding boron to hydrofinishing catalysts, in which boron is added to the catalytic precursor in a separate step, is responsible for the tendency of boron to leach out under the operating conditions of activation, startup and operation of industrial hydrofining equipment.
[0021] Therefore, the main problem associated with the use of boron as an additive is its tendency to leach out under start-up and operating conditions of industrial hydrotreating plants, resulting in a substantial loss of the increased catalytic activity and stability provided by the presence of boron. Leaching also causes the release of boron into the environment, resulting in deleterious effects on the environment, which have been reported in the specialist literature.
[0022] In order to solve such problems, the present invention was developed, wherein a method for obtaining a support by an innovative preparation route is proposed, which reduces the problem of loss of boron (or chemical derivatives containing boron) over time (or leaching or related loss processes). In the presence of boron in the catalyst, the activity (hydrogenation and acidity) and stability towards hydrofining reactions (hydrotreating and hydrocracking) are significantly increased.
[0023] Furthermore, the fixation of boron in the catalyst ensures the maintenance of its properties during operation throughout the entire operation of the industrial plant. Additionally, it minimizes the release of boron to the environment and the contamination of medical and food grade paraffins and lubricating base oils from the hydrofinishing process using catalysts with boron additives.
[0024] It is therefore determined that the foregoing relates to catalysts, catalytic compositions and methods for producing catalyst support materials and / or the catalysts themselves, but fail to address the problem of boron losses. Summary of the invention
[0025] The object of the present invention is to obtain a support by an innovative preparation route, which reduces the problem of boron loss over time due to leaching or related processes (as observed in catalysts and supports obtained by the prior art). Since the presence of boron in the catalyst brings the properties of increased activity (hydrogenation and acidity) and stability to the hydrofinishing reactions (hydrotreating and hydrocracking), the retention of boron in the catalyst ensures the maintenance of the operating characteristics throughout the operation of the entire industrial plant. Additionally, in the case of using a catalyst resistant to boron leaching, the pollution of the environment and the contamination of medical and food grade paraffin and lubricating base oils from the hydrofinishing process are minimized. DETAILED DESCRIPTION
[0026] In particular, the present invention relates to a method of obtaining a support by an innovative preparation route, which reduces the problem of boron loss (or leaching) over time. The support can be applied in the synthesis of catalysts for use in hydrofining processes.
[0027] Boron is understood to mean all chemical derivatives (substances and molecules) which contain the chemical element boron in their composition.
[0028] Preferably, the carrier obtained by the method protected herein is applied to the catalyst for hydrofining process, mainly olefin hydrogenation, hydrodemetallization, hydrodesulfurization, hydrodenitrogenation, hydrodearomatization and hydrocracking. The reaction can occur alone or together. The treated feed can have a mineral source (oil fraction with a wide distillation range, from naphtha to residues, until lubricating base oils and paraffins), with a renewable source (pyrolysis bio-oil, vegetable oil, oil from biomass processing, biomass in its natural state), from an upstream process (e.g., distillates and paraffins obtained from the Fischer-Tropsch process (gas to liquid (Gas-to-liquid), GTL) and mixtures thereof.
[0029] Hydroprocessing catalysts include materials consisting of an oxidized hydrogenation phase (at least one element in Group VIII (IUPAC) and / or at least one element in Group VIB (IUPAC) and a mixture of the two) supported in an inert matrix and / or having some acid-base activity (alumina, silica-alumina, zeolite, silica, titania, zirconium oxide, magnesium oxide, clay, hydrotalcite, etc.) and / or additives that promote acidic functions or specific properties, such as boron-based and phosphorus-based compounds. The catalyst is active in sulfided form. Other possibilities for hydroprocessing catalysts include the use of noble metals (Pt, Pd, Rh, Ir, Ru, pure or polymetallic) as hydrogenation phases. In this case, these are active in reduced form. The operating conditions of the hydrotreating process include a H partial pressure of 1 bar to 200 bar (0.1 MPa to 20 MPa), preferably 40 bar to 150 bar (4 MPa to 15 MPa), more preferably 50 bar to 120 bar (5 MPa to 12 MPa); a temperature of 200° C. to 450° C., preferably 320° C. to 430° C., more preferably 340° C. to 410° C.; and a 0.1 hour -1 Up to 5 hours -1 , preferably 0.2 hours -1 Up to 3.0 hours -1 , more preferably 0.3 hours -1 Up to 2.0 hours -1 The volume space velocity (liquid hourly space velocity - LHSV - (ratio between the feed volume flow rate and the catalyst volume)). The hydrocracking catalyst comprises a material consisting of an oxidized hydrogenation phase (at least one element of group VIII (IUPAC) and / or at least one element of group VIB (IUPAC) and a mixture of both) supported in an inert matrix and / or having some acid activity (alumina, silica-alumina, zeolites, silica, titania, zirconia, etc.) and / or additives with acidic functions or specific properties, such as boron-based and phosphorus-based compounds. The catalyst is activated by sulfidation. Other possibilities for hydrocracking catalysts include the use of noble metals (Pt, Pd, Rh, Ir, Ru, pure or multimetallic) as hydrogenation phase. In this case, these are active in reduced form. The operating conditions of the hydrocracking process include a H2 partial pressure of 1 bar to 200 bar (0.1 MPa to 20 MPa), preferably 40 bar to 150 bar (4 MPa to 15 MPa), more preferably 50 bar to 120 bar (5 MPa to 12 MPa); a temperature of 200°C to 450°C, preferably 320°C to 430°C, more preferably 340°C to 410°C; and a 0.1 hour -1 Up to 5 hours -1 , preferably 0.2 hours -1 Up to 3.0 hours-1 , more preferably 0.3 hours -1 Up to 2.0 hours -1 LHSV.
[0030] In a first aspect, the present invention relates to a method for obtaining a support for a hydrofinishing catalyst by an acidic route, the method comprising the steps of:
[0031] (a) mixing an aluminum source, an organic acid and a boron source;
[0032] (b) adding sufficient deionized water to mix the reactants;
[0033] (c) heating the mixture obtained in step (b) at 25°C to 60°C, preferably 30°C to 50°C, more preferably 30°C to 35°C, for 5 minutes to 60 minutes, preferably 5 minutes to 30 minutes, more preferably 5 minutes to 10 minutes;
[0034] (d) homogenizing the reactants under stirring;
[0035] (e) heating the mixture obtained in step (d) to 60°C to 80°C, preferably 60°C to 70°C, more preferably 60°C to 65°C, and maintaining for 1 hour to 4 hours, preferably 1 hour to 2 hours, more preferably 1 hour;
[0036] (f) raising the temperature of the mixture obtained in step (e) to 80°C to 120°C, preferably to 80°C to 100°C, more preferably to 80°C to 85°C, and maintaining it for 1 hour to 3 hours, preferably 1 hour to 2 hours, more preferably 1 hour to 1.5 hours;
[0037] (g) stopping stirring and heating and allowing the sample to cool to room temperature;
[0038] (h) drying the material obtained in step (g) at 80°C to 120°C, preferably 100°C to 120°C, more preferably 115°C to 120°C, for up to 8 hours, preferably up to 6 hours, more preferably up to 4 hours;
[0039] (i) calcining the material obtained in step (f) at 500 to 800°C, preferably at 600 to 800°C, more preferably at 700 to 710°C, for up to 6 hours, preferably up to 4 hours, more preferably up to 3 hours.
[0040] In this regard, the pH of the mixture was measured at intervals of 30 minutes starting from the moment the mixture reached a temperature of 60° C. to 65° C. (step (e)).
[0041] Furthermore, in this aspect, the mixing of the aluminum source and the organic acid must be carried out in an X / Y molar ratio, wherein X is the aluminum source and Y is the organic acid. The molar ratio may be 10 / 1 to 1 / 10, preferably 5 / 1 to 1 / 5, more preferably 2 / 1 to 1 / 2.
[0042] The boron source is added so that the boron content expressed as oxide (B2O3) and based on the total support mass may be 0.1 to 10 mass%, preferably 0.5 to 8 mass%, more preferably 1 to 5 mass% of the final support.
[0043] Furthermore, in this aspect, the aluminum source may be a pure substance or a mixture with each other, and may include an aluminum-based compound, preferably aluminum chloride, aluminum sulfate, aluminum isopropoxide, aluminum nitrate, and more preferably aluminum nitrate.
[0044] Furthermore, in this aspect, the organic acid may be a pure substance or a mixture with each other, and may include a carboxylic acid containing 1 to 6 carbon atoms, preferably containing 1 to 4 carbon atoms, more preferably acetic acid.
[0045] Furthermore, in this aspect, the boron source may be a pure substance or a mixture with each other, and may include boron-based compounds; metaboric acid (HBO2); orthoboric acid (H3BO3); ammonium borate tetrahydrate [(NH4)2B4O7.4H2O]; sodium tetraborate; ammonium borate; ammonium tetraborate; boric oxide (B2O3); various monoalkylaminoborates, dialkylaminoborates and trialkylaminoborates; tetraphenylammonium borate; and the like.
[0046] In the same reported aspect, supplemented is the fact that the acidic route is carried out in a vessel inside which the reactants are stirred and heated, preferably a reactor with circulating heating.
[0047] Further with respect to this reported aspect, the mixing of the aluminum source, organic acid, and boron source is performed in a reactor having circulating heating.
[0048] In the second aspect, the support is composed of an aluminum source, an organic acid and a boron source, and is obtained according to the above method.
[0049] With regard to the second invention aspect, it is important to emphasize that the carrier described herein has 80 m 2 / g to 250m 2 / g, preferably 100m 2 / g to 230m 2 / g, more preferably 150m 2 / g to 200m 2 / g specific area.
[0050] Furthermore, in this second aspect, the support constitutes the preparation of a hydrofinishing catalyst (hydrotreating and hydrocracking).
[0051] In addition, in this second aspect, the hydroprocessing catalyst comprises the following material, which consists of a hydrogenation phase in an oxidized form (at least one element in Group VIII (IUPAC) and / or at least one element in Group VIB (IUPAC) and a mixture of the two) supported on a support that is the subject of the present invention, and the support may or may not be associated with an inert matrix and / or may or may not be associated with some acid-base activity (alumina, silica-alumina, zeolite, silica, titania, zirconium oxide, magnesium oxide, clay, hydrotalcite, etc.) and / or may or may not be associated with additives that promote acidic functions or specific properties (for example, boron-based and phosphorus-based compounds). The catalyst is active in sulfided form. Other possibilities for hydroprocessing catalysts include the use of noble metals (Pt, Pd, Rh, Ir, Ru, pure or polymetallic) as hydrogenation phases. In this case, these are active in reduced form.
[0052] Moreover, in this second aspect, for the hydrocracking catalyst, the material consists of a hydrogenation phase in oxidized form (at least one element of group VIII (IUPAC) and / or at least one element of group VIB (IUPAC) and a mixture of both) supported on a support that is the subject of the invention, which support may or may not be associated with an inert matrix and / or may or may not be associated with some acid activity (alumina, silica-alumina, zeolites, silica, titania, zirconium oxide, etc.) and / or may or may not be associated with additives that promote acidic functions or specific properties (for example boron-based and phosphorus-based compounds). The catalyst is activated by sulfidation. Other possibilities for hydrocracking catalysts include the use of noble metals (Pt, Pd, Rh, Ir, Ru, pure or polymetallic) as hydrogenation phase. In this case, these are active in reduced form.
[0053] Furthermore, in this second aspect, the content of the hydrogenation phase of the active hydrorefining catalyst in a sulfided form, expressed as the total loading of oxides and relative to the total mass of the final catalyst, may be 0.5 to 10% by mass of components of Group VIII (in pure form or in a mixture with one another) and 5 to 30% by mass of components of Group VIB (in pure form or in a mixture with one another).
[0054] Furthermore, in this second aspect, the content of the hydrogenation phase of the active hydrorefining catalyst in reduced form, expressed as the total loading of the precious metals and relative to the total mass of the final catalyst, may be 0.1% by mass to 20% by mass of precious metals (Pt, Pd, Rh, Ir, Ru) (either in pure form or in a mixture with one another).
[0055] The second aspect of the invention also consists in the fact that, in the preparation of the hydrofinishing catalyst, the hydrogenation phase is introduced into the support with or without pH adjustment.
[0056] As regards the second aspect of the present invention, it is also noted that the support obtained by the process described in the present invention is used to improve the performance of catalysts based on boron and alumina by preventing the leaching of boron.
[0057] In the third aspect of the present invention, it is noted that the supported catalyst is obtained by the following steps:
[0058] (a) preparing a homogenous aqueous solution comprising one or more elements of group VIII, satisfying the wet-point impregnation requirements of the support that is the subject of the present invention and providing a total loading of the components of group VIII (pure or in admixture with one another) of 0.5 to 10% by mass of the final catalyst (as oxides and relative to the final mass of the catalyst);
[0059] (b) adding to the mixture from step (a) an amount of phosphoric acid, not limited to the particular phosphorus source, sufficient to provide a final catalyst with 0.1 mass % to 3.0 mass % phosphorus present;
[0060] (c) stirring the mixture obtained in step (b) until any form of foam disappears;
[0061] (d) adding one or more elements from Group VIB in a total loading sufficient to make the Group VIB components (pure substances or in mixtures therebetween) comprise 5 to 30 mass % of the final catalyst (as oxidants and relative to the final mass of the catalyst);
[0062] (e) achieving a sufficient volume for wet spot impregnation of the support which is the subject of the present invention and heating the system to 80°C to 100°C, preferably 80°C to 95°C, more preferably 90°C to 95°C;
[0063] (f) stirring the system until dissolution is complete;
[0064] (g) cooling the system and impregnating at the wet point an amount of the support which is the subject of the present invention to satisfy the total loading of elements of Group VIII and Group VIB in the final catalyst.
[0065] In this third aspect of the invention, the supported catalyst is cooled and the pH is adjusted to 2.0 to 4.0, preferably 2.0 to 3.0, more preferably 2.5 to 3.0, using ammonium hydroxide.
[0066] Furthermore, in this third aspect, the solution must be added to the support under stirring, after which it is allowed to stand for 1 hour with occasional stirring.
[0067] It should be noted that in the third aspect of the invention, the precursor is dried at 80° C. to 120° C. for 1 to 2 hours and then calcined at 400° C. to 700° C. for 1 to 2 hours.
[0068] It remains to be stated that the support which is the subject of the present invention can be impregnated at the wet point with the noble metals (sources of Pt, Pd, Rh, Ir and Ru) either pure or in mixture with one another.
[0069] Example
[0070] Example 1
[0071] Preparation of a reference support: The support was prepared by mixing hydrated alumina with boric acid (H3BO3) in a mixer to form a slurry. The water can be evaporated or added to adjust the slurry for extrusion. After extrusion, the support was dried at 120°C overnight and calcined at 700°C to obtain a final B2O3 concentration of 3.75% by mass. This support will be referred to as SUPREF hereinafter.
[0072] Example 2
[0073] The support as the subject of the present invention was prepared by an acidic route: Aluminum nitrate and acetic acid (510 g and 80 mL, respectively) in a 1:1 molar ratio were mixed with 3.8 g of boric acid in a reactor with circulating heating. Then, a sufficient volume of deionized water was added to mix the reactants. The mixture was heated at 30°C for 5 to 10 minutes under stirring to completely homogenize the reactants. Then, the temperature was raised to 60°C and maintained for 1 hour. After this time, the temperature was raised to 80°C and maintained under this condition for 1.5 hours. During the reaction, the pH of the mixture was measured at intervals of 30 minutes starting from the moment the temperature reached 60°C. Then, stirring and heating were stopped and the sample was allowed to cool overnight.
[0074] The material was dried at 120° C. for 4 hours and then the sample was calcined at a temperature of 700° C. for 3 hours. This sample is referred to as SUP1 hereinafter.
[0075] Example 3
[0076] Catalyst preparation without pH adjustment: The catalyst was prepared using the support of Example 2, hereinafter referred to as CAT1. 6.0 g of nickel carbonate (NiCO3.2Ni(OH)2.4H2O) was added to 5 ml of stirred water, followed by 5.1 g of phosphoric acid, and stirring was maintained to minimize the release of foam.
[0077] After the foam release ceased, 18.4 g of molybdenum oxide (MoO3) was added to complete the volume of the solution to 20 ml, and the system was heated to 95°C, maintaining the system under stirring and reflux until complete dissolution.
[0078] Next, the solution was then allowed to cool and 67 g of the support was impregnated. The solution was added to the support under stirring, after which it was left to stand for 1 hour with occasional stirring. The precursor was then dried at 120°C for 1 hour and then calcined at 450°C for 1 hour. The final content in the catalyst is shown in Table 1 below.
[0079] Table 1 : Final content in CAT1 catalyst
[0080] Content (mass %) NiO 4.0 <![CDATA[MoO3]]> 20 P% 1.5
[0081] Example 4
[0082] -Preparation of catalyst with pH adjustment: The catalyst was prepared using the support of Example 2, hereinafter referred to as CAT2. 6.0 g of nickel carbonate (NiCO3.2Ni(OH)2.4H2O) was added to 5 ml of stirred water, and then 5.1 g of phosphoric acid was slowly added while stirring to minimize foaming. In this case, we waited for the foam to disappear and then added 18.4 g of molybdenum oxide (MoO3). The volume of the solution was then replenished to 20 ml, the system was heated to 95°C, and the system was stirred and refluxed until completely dissolved. The solution was then cooled and the pH was measured, which should be adjusted to 2.5 using ammonium hydroxide. Afterwards, 67 g of the support can be impregnated. The solution should be added to the support with stirring, after which it was left to stand for 1 hour with occasional stirring. The precursor was then dried at 120°C for 1 hour and then calcined at 450°C for 1 hour. The final content in the catalyst is shown in Table 2 below.
[0083] Table 2 : Final content in CAT2 catalyst
[0084] Content (mass %) NiO%m 4.0 <![CDATA[MoO3%m]]> 20 P%m 1.5
[0085] Example 5
[0086] Commercial Catalyst: A commercial catalyst for hydroprocessing used to produce ultra-low sulfur diesel was used as a reference, hereinafter referred to as CATREF1.
[0087] Example 6
[0088] -Extraction with deionized water: About 2 g of the catalyst and support to be evaluated with a particle size analysis of 150 mesh to 325 mesh are weighed. Each extraction is carried out separately using a Soxhelt installed according to ASTM D5369-93 and the samples are washed with water. The extraction is continued for a period of 2 hours when the temperature reaches 100°C. After the extraction, the system is turned off and cooled. In the case of a cold system, the catalyst and support are dried in porcelain capsules at 120°C for 18 hours. All supports and catalysts after treatment keep the original names, but the term "-2 hours" is added at the end of the name to indicate that they are after the extraction process with deionized water. Therefore SUP1 is called SUP1-2 hours after leaching.
[0089] Example 7
[0090] Boron loss after leaching of the support: The results for the reference support SUPREF support prepared as described in Example 1 and the support SUP1 which is the subject of the present patent prepared as described in Example 2 are shown in Table 3. Both supports lose boron under the conditions evaluated, but while the reference support suffers a reduction of about 77% by mass of the boron content of the original support after leaching, the support which is the subject of the present patent suffers a reduction of only about 51% by mass. Compared to the support prepared by conventional methods, the reduction in boron loss is almost 30%.
[0091] Table 3
[0092] Results of boron content of the carrier prepared in this patent and the reference carrier before and after extraction.
[0093]
[0094] Example 8
[0095] The specific area is crucial for the hydrofining process. The area of the SUPREF carrier is 195m 2 / g and the area of SUP1 is 187m 2 / g, indicating that the proposed preparation method has the advantage of fixing boron without any detrimental loss in specific area.
[0096] Example 9
[0097] Boron losses after leaching of the catalysts: For the reference catalyst CATREF1 and the catalysts prepared from the support that is the subject of the present patent (CAT1 and CAT2), the same leaching procedure described in Example 6 was used. The boron losses of the prepared catalysts and the reference catalysts are shown in Table 4, expressed as initial and final B2O3 masses calculated relative to the support.
[0098] Table 4 presents the results of the B2O3 content of the catalyst prepared in the present invention and the commercial reference catalyst before and after extraction. Under the evaluation conditions, the mass loss of B2O3 from the commercial catalyst was about 71%, while the losses of the catalyst prepared without pH adjustment and with pH adjustment were about 18% and 21%, respectively. In this way, it is demonstrated that the preparation method of the support fixes boron therein, and additionally, the preparation steps of the catalyst still help to reduce the loss of boron in the support and therefore reduce the loss of boron in the final catalyst. For boron fixation, the pH effect of the final catalyst preparation is not significant, so adjustment may or may not be used as a step in the catalyst preparation.
[0099] Table 4: Comparison between B2O3 content results before and after extraction
[0100]
[0101] Therefore, the present invention proposes a method for maintaining the activity of a hydrotreating catalyst over time, maintaining the productivity of the equipment over time, and reducing operating costs by focusing on the use of activity and catalyst stability.
[0102] The present invention has the potential to apply these catalysts to industrial plants for: hydroprocessing of naphtha (gasoline), kerosene, diesel, paraffin, lubricants; catalytic reforming pretreatment; solvent hydrogenation; delayed coker naphtha hydrogenation; pretreatment of feeds from catalytic cracking plants (FCC); pretreatment and hydrocracking of industrial hydrocracking plants for diesel; hydroprocessing of general residues; etc.
[0103] Therefore, the addition of boron to the catalyst and its retention allows the hydrotreating unit to operate at high performance throughout its operation, helping to improve refining profits and helping as a technical solution to equalize the production of S10 diesel and jet fuel as the share of S10 diesel increases.
[0104] Such a hydrofinishing catalyst with acid cracking activity allows processing of heavier feeds (95% temperature reduction of vaporization by volume in distillation ASTM D-86), minimizing production losses caused by 100% market service S10 diesel. More active catalysts can also be used for export grade diesel production (EN-590) opportunities in existing high intensity equipment.
Claims
1. A method for obtaining a carrier for a hydrotreating catalyst, characterized in that the method comprises the following steps: (a) mixing an aluminum source, an organic acid and a boron source; (b) adding sufficient deionized water to mix the reactants; (c) heating the mixture obtained in step (b) at 25° C. to 60° C. for 5 to 60 minutes; (d) homogenizing the reactants under stirring; (e) heating the mixture obtained in step (d) to 60° C. to 80° C. and maintaining for 1 to 4 hours; (f) raising the temperature of the mixture obtained in step (e) to 80° C. to 120° C. and maintaining it for 1 to 3 hours; (g) stopping stirring and heating and allowing the sample to cool to room temperature; (h) drying the material obtained in step (g) at 80°C to 120°C for up to 8 hours; (i) calcining the material obtained in step (f) at 500° C. to 800° C. for up to 6 hours, Characterized in that the mixing of the aluminum source and the organic acid must be carried out in an X / Y molar ratio, wherein X is the aluminum source and Y is the organic acid, wherein the molar ratio can be 10 / 1 to 1 / 10, Characterized in that the boron source is added so that the boron content expressed as oxide B2O3 and based on the total support mass can be 0.1 mass % to 10 mass % of the final support, and The organic acid can be a pure substance or a mixture, and the organic acid can include a carboxylic acid containing 1 to 6 carbon atoms.
2. The method according to claim 1, characterized in that in step (c), the mixture obtained in step (b) is heated at 30°C to 50°C for 5 minutes to 30 minutes.
3. The method according to claim 1, characterized in that in step (c), the mixture obtained in step (b) is heated at 30°C to 35°C for 5 to 10 minutes.
4. The method according to claim 1, characterized in that in step (e), the mixture obtained in step (d) is heated to 60°C to 70°C and maintained for 1 hour to 2 hours.
5. The method according to claim 1, characterized in that in step (e), the mixture obtained in step (d) is heated to 60°C to 65°C and maintained for 1 hour.
6. The method according to claim 1, characterized in that in step (f), the temperature of the mixture obtained in step (e) is increased to 80°C to 100°C and maintained for 1 hour to 2 hours.
7. The method according to claim 1, characterized in that in step (f), the temperature of the mixture obtained in step (e) is increased to 80°C to 85°C and maintained for 1 hour to 1.5 hours.
8. The method according to claim 1, characterized in that in step (h), the material obtained in step (g) is dried at 100°C to 120°C for up to 6 hours.
9. The process according to claim 1, characterized in that in step (h), the material obtained in step (g) is dried at 115°C to 120°C for up to 4 hours.
10. The method according to claim 1, characterized in that in step (i), the material obtained in step (f) is calcined at 600 to 800°C for up to 4 hours.
11. The method according to claim 1, characterized in that in step (i), the material obtained in step (f) is calcined at 700°C to 710°C for up to 3 hours.
12. The method according to claim 1, characterized in that the molar ratio can be 5 / 1 to 1 / 5.
13. The method according to claim 1, characterized in that the molar ratio can be 2 / 1 to 1 / 2.
14. The method according to claim 1, characterized in that the boron content can be between 0.5% and 8% by mass of the final support.
15. The method according to claim 1, characterized in that the boron content can be 1% to 5% by mass of the final support.
16. The method of claim 1, characterized in that the organic acid can include a carboxylic acid containing 1 to 4 carbon atoms.
17. The method of claim 1, wherein the organic acid can include acetic acid.
18. The method according to claim 1, characterized in that the pH of the mixture is measured at intervals of 30 minutes starting from the moment the mixture reaches a temperature of 60°C.
19. The method according to claim 1, characterized in that the aluminum source can be a pure substance or a mixture and can include aluminum-based compounds.
20. The method of claim 1, characterized in that the aluminum source can be a pure substance or a mixture and can include aluminum chloride, aluminum sulfate, aluminum isopropoxide or aluminum nitrate.
21. The method of claim 1, wherein the aluminum source can be a pure substance or a mixture and can include aluminum nitrate.
22. The method of claim 1, characterized in that the boron source can be a pure substance or a mixture and can include a boron-based compound.
23. The method according to claim 1, characterized in that the boron source can be a pure substance or a mixture and can include metaboric acid; orthoboric acid; ammonium borate tetrahydrate; sodium tetraborate; ammonium borate; ammonium tetraborate; boric oxide; various monoalkylaminoborates or monoalkylaminoborates, dialkylaminoborates or dialkylaminoborates and trialkylaminoborates or trialkylaminoborates; or tetraphenylammonium borate.
24. The process according to claim 1, characterized in that the acidic route is carried out in a vessel inside which stirring and heating of the reactants are carried out.
25. The process according to claim 1, characterized in that the acid route is carried out in a reactor with circulating heating.
26. The method according to claim 1, characterized in that the mixing of the aluminum source, the organic acid and the boron source is carried out in a reactor with circulating heating.
27. A support obtained according to the method according to any one of claims 1 to 26, characterized in that the support consists of an aluminum source, an organic acid and a boron source.
28. The support according to claim 27, characterized in that the support constitutes the preparation of a hydrofinishing catalyst.
29. The carrier according to claim 27, characterized in that the specific area of the carrier is 80 m 2 / g to 250m 2 / g.
30. The carrier according to claim 27, characterized in that the specific area of the carrier is 100m 2 / g to 230m 2 / g.
31. The carrier according to claim 27, characterized in that the specific area of the carrier is 150 m 2 / g to 200m 2 / g.
32. The support according to claim 27, characterized in that it improves the performance of catalysts based on boron and alumina by preventing boron leaching.
33. A hydrotreating catalyst, characterized in that the hydrotreating catalyst uses the carrier according to any one of claims 27 to 32.
34. A method for obtaining a hydrotreating catalyst, characterized in that the method comprises the following steps: (a) preparing a homogeneous aqueous solution comprising one or more elements of group VIII, satisfying the wet spot impregnation requirements of the support obtained according to the method of any one of claims 1 to 26, and wherein the total loading of the components of group VIII in terms of oxide relative to the final mass of the catalyst is 0.5 to 10% by mass of the final catalyst, wherein the components of group VIII are in pure form or in mixture; (b) adding to the mixture from step (a) an amount of a phosphorus source sufficient to provide a final catalyst with 0.1 mass % to 3.0 mass % phosphorus present; (c) stirring the mixture obtained in step (b) until any form of foam disappears; (d) adding one or more elements from Group VIB in a total loading sufficient to make the Group VIB components account for 5% to 30% by mass of the final catalyst as oxides relative to the final mass of the catalyst, wherein the Group VIB components are in pure form or in mixture; (e) completing a sufficient volume of wet spot impregnation of a support obtained according to the process of any one of claims 1 to 26, and heating the resulting system to 80° C. to 100° C.; (f) stirring the system until dissolution is complete; (g) cooling the system and impregnating an amount of the support obtained according to the method according to any one of claims 1 to 26 at the wet point to satisfy the total loading of elements of Group VIII and Group VIB in the final catalyst.
35. The method according to claim 34, characterized in that the phosphorus source is phosphoric acid.
36. The method according to claim 34, characterized in that in step (e), the obtained system is heated to 80°C to 95°C.
37. The method according to claim 34, characterized in that in step (e), the obtained system is heated to 90°C to 95°C.
38. The process according to claim 34, characterized in that the supported catalyst is cooled and the pH is adjusted to 2.0 to 4.0 using ammonium hydroxide.
39. The process according to claim 34, characterized in that the supported catalyst is cooled and the pH is adjusted to 2.0 to 3.0 using ammonium hydroxide.
40. The process according to claim 34, characterized in that the supported catalyst is cooled and the pH is adjusted to 2.5 to 3.0 using ammonium hydroxide.
41. Process according to any one of claims 34 and 38, characterised in that the solution must be added to the support under stirring, after which it is left to stand for 1 to 4 hours with occasional stirring.
42. Process according to any one of claims 34 and 38, characterised in that the solution must be added to the support under stirring, after which it is left to stand for 1 to 3 hours with occasional stirring.
43. Process according to any one of claims 34 and 38, characterised in that the solution must be added to the support with stirring, after which it is left to stand for 1 hour to 1.5 hours with occasional stirring.
44. The method according to any one of claims 34 and 38, characterized in that the precursor is dried at 80 to 120°C for 1 to 2 hours and then calcined at 400 to 700°C for 1 to 2 hours, wherein in addition, the support can be impregnated with pure noble metals or mixtures thereof at the wet point.
45. The method according to claim 44, characterized in that the source of the noble metal is Pt, Pd, Rh, Ir and Ru.
46. Use of a carrier according to any one of claims 27 to 32, characterized in that the carrier is used for the impregnation of a hydrofinishing catalyst to reduce the boron leaching process.
Citation Information
Patent Citations
Heavy oil hydrogenating treatment catalyst and preparation method thereof
CN101332430A
Heavy oil hydrotreating composite catalyst preparation method
CN102989493A
Catalyst composition preparation and use
US20120065056A1
Aluminum borate catalyst compositions and use thereof in chemical conversions
US4034061A
Hydroprocessing catalyst
US4672049A